Multiplex polymerase chain reaction (PCR) with Nanopore sequencing for sequence-based detection of four tilapia pathogens - Delamare-Deboutteville, Jerome; Meemetta, Watcharachai; Pimsannil, Khaettareeya; Han Ming, Gan; Khor, Laura; Chadag, Vishnumurthy Mohan; Thanh, Dong Ha; Saengchan, Senapin (PeerJ, 2025)
Background: Tilapia aquaculture faces significant threats posed by four prominentpathogens: tilapia lake virus (TiLV), infectious spleen and kidney necrosis virus (ISKNV), Francisella orientalis, and Streptococcus agalactiae. Currently, employed molecular diagnostic methods for these pathogens rely on multiple singleplex polymerase chain reactions (PCR), which are time-consuming and expensive. Methods: In this study, we present an approach utilizing a multiplex PCR (mPCR) assay, coupled with rapid Nanopore sequencing, enabling the one-tube simultaneous detection and one-reaction Nanopore sequencing-based validation of four pathogens. Results: Our one-tube multiplex assay exhibits a detection limit of 1,000 copies per reaction for TiLV, ISKNV, and S. agalactiae, while for F. orientalis, the detection limit is 10,000 copies per reaction. This sensitivity is sufficient for diagnosing infections and co-infections in clinical samples from sick fish, enabling rapid confirmation of the presence of pathogens. Integrating multiplex PCR and Nanopore sequencing provides an alternative approach platform for fast and precise diagnostics of major tilapia pathogens in clinically sick animals, adding to the available toolbox for disease diagnostics.